The Effect of Rice Husk Addition as Additive Materials on the Characterization of Ceramic Membrane and Their Application on Water River Treatment Process - Sisnayati Sisnayati; Ria Komala; Retno Suryani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2019)
This study aims to study how the effect of adding rice husk additives to the characteristics of ceramic membranes with various variations of membrane-forming component composition in terms of surface morphology and pore size of the membrane produced. This research is expected to be used by the community as an alternative treatment of river water into clean water. In this study, the variables studied were the composition of the membrane constituent namely clay, iron powder and rice husk as an additives. The ceramic membrane was designed in the form of a tube, made from a mixture of clay, iron powder and rice husk with a diameter of 5 cm, an outer diameter of 6 cm, a thickness of 1 cm and a length of 25 cm. Housing membrane was made of glass fiber with an outer diameter of 9 cm, an inner diameter of 8.5 cm and a length of 30 cm. Making ceramic membranes were from clay, iron powder and rice husk with a ratio of 87.5%, 2.5%, 10%, 77.5%, 2.5%, 20% and 77.5%, 2.5%, 15%. The river water was treated by flowing to the complete separation process. It was taken every 15 minutes, 30 minutes, 45 minutes, 60 minutes, 75 minutes, 90 minutes. Every sampling, the permeate volume was determined. Permeat events were analyzed for chemical parameters in the form of iron (Fe), Manganese (Mn) and Zinc (Zn). Based on the SEM-EDS analysis on the ceramic membrane produced shows that the membrane was classified in the microfiltration membrane group with a random and asymmetrical pore size and structure. According to the BET analysis on ceramic membranes shows that the best ceramic membrane produced in this study is C ceramic membrane with a clay composition of 87.5%; 10% of rice husk; and 2.5% of iron powder with a pore size of 2.8 μm and a large surface area of ​​45.38 m2/g. The difference in pressure of 2 bars gives the best results in reducing levels of contaminant compounds contained in river water with a percentage of Fe reduction of 92.18%, Mn of 89.23%, and Zn of 99.80%.